Analysis of Financial Ratios to Measure Financial Performance in the Oil and Gas Industry Listed on the Indonesia Stock Exchange for the Period 2017-2021 - Kurnia, Annisa Desri; Sundarta, M. Imam; Yudiana (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the financial performance of oil and gas companies listed on the IDX for the 2017-2021 period. This type of research is a descriptive qualitative research with secondary data, namely in the form of financial reports of oil and gas companies listed on the IDX obtained from the website www.idx.co.id with time series and cross sectional analysis. The samples used in this study are three oil and gas companies listed on the IDX for the 2017-2021 period, namely PT. Astrindo Nusantara Infrastructure Tbk, PT. Elnusa Tbk and PT. Main radiant interinsco Tbk with sampling technique using purposive sampling method. Analysis of the data used is the analysis of financial ratios. The results showed that in the ratio analysis of the overall company finances which became the object of research the company had a good performance.